A national epidemiological survey of oral mucosal lesions in Malaysia - Zain, R.B.; Ikeda, N.; Razak, I.A.; Axell, T.; Majid, Z.A.; Gupta, P.C.; Yaacob, M. (Blackwell Publishing, 1997)
The prevalence of oral mucosal lesions in Malaysia was determined by examining a representative sample of 11 707 subjects aged 25 years and above throughout the 14 states over a period of 5 months during 1993/1994. A two-stage stratified random sampling was undertaken. A predetermined number of enumeration blocks, the smallest population unit in the census publication was selected from each state. With the selected enumeration block, a systematic sample of living quarters was chosen with a random start. The survey instrument included a questionnaire on sociodemographic characteristics and a clinical examination. The clinical examination was carried out by 16 specially trained dental public health officers and the diagnosis calibrated with a final concordance rate of 92. The age in the sample ranged from 25 to 115 years with a mean of 44.5+14.0. The sample comprised 40.2 males and 59.8 females; 55.8. were Malays, 29.4 Chinese,10.0 Indians and 1.2 other ethnic groups. Oral mucosal lesions were detected in 1131 (9.7.) subjects. 5 (0.04) had oral cancer, 165 (1.4) had lesions or conditions that may be precancerous (leukoplakia. erythroplakia, submucous fibrosis and lichen planus) and 187 (1.6) had betel chewer's mucosa. The prevalence of oral precancer was highest amongst Indians (4.0) and other Bumiputras (the indigenous people of Sabah and Sarawak) (2.5) while the lowest prevalence was amongst the Chinese (0.5).